Pulsed Ion Beam Induced Changes in a Topography of the Surface Layers of Titanium; Surface Modification of Materials by Ion Beams (SMMIB-2019) - Ligachev A. Alexander; Zhidkov M. V.; Kolobov Y. R.; Potemkin G. V. Gely Valerjyanovich (Ion Beam Processing of Materials. Poster Session, 2019)
Заглавие с экрана